PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE LISTENING TEAM TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 15 PADANG TAHUN PELAJARAN 2013/2014 - helda, Arsu; Zulfaneti, Zulfaneti; Fitri, Dewi Yuliana (STKIP PGRI Sumbar, 2013)
The background of this research was concept undertanding of students toward math that can be seen through the studentsâ mathematics results grade VIII SMP 15 year 2013/2014 are still low. The purpose of this research is to see âis studentsâ undertanding toward math concept that implemented active learning type listening better thatÂ conventional class?â. This study is a kind of experiment research that is subject random design. The population of the subject is student at SMP 15 year 2013/2014 grade VIII. The sample of this research is VIII.3 as experiment class VIII.5 as control class. The instrument of this research is test of mathematic concept. The form of the test that was used is essay test. The reliability of the test is r11= 0,814. To analyze the data the researcher used T-test that used sofware Minitab in analyzing it. Based on the result of the research, it is found that both of sample with normal distribution and homogeny, the reliability is Â and the result of the hipothesis is the value of P equal 0,001, . It means that the hypothesis of this research is accepted. It can be concluded that math concept understanding of the students who implement active learning strategy type listening team is better than the student who learned with onventional strategy confidence intervalsÂ 95% at SMP 15 Padang grade VIII.Â Â Â Â Â Â Â Â Â Â Â Â